2008
DOI: 10.1177/070674370805300407
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Characteristics of Psychiatric Outpatients

Abstract: Unhealthy lifestyle issues are not restricted to any specific diagnostic group. These data identify a compelling need to develop ameliorative intervention strategies for psychiatric outpatients; however, we could not identify a basis for targeting such interventions specifically in relation to diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 13 publications
0
26
0
3
Order By: Relevance
“…This limitation of classical PK methodology should therefore be considered, especially in patients with schizophrenia, given their altered lifestyle. 15 In contrast, one of the major advantages of population PK methodology over the traditional one is that it relies on the use of data collected in a real-world clinical setting. Indeed, in the present study, 2 plasma samples were collected at given time points in daily clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…This limitation of classical PK methodology should therefore be considered, especially in patients with schizophrenia, given their altered lifestyle. 15 In contrast, one of the major advantages of population PK methodology over the traditional one is that it relies on the use of data collected in a real-world clinical setting. Indeed, in the present study, 2 plasma samples were collected at given time points in daily clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…182 People with MDD or depressive symptoms are more likely to be sedentary relative to those without mood disorders. [183][184][185] The association of physical activity with BD is inconsistent. Some studies have demonstrated reduced physical activity and reduced exercise tolerance in BD, 186,187 whereas other studies have demonstrated no significant differences.…”
Section: Sedentary Lifestylementioning
confidence: 99%
“…19 studies utilised SRQs Archie et al, 2007Arbour, Faulkner, & Cohn, 2010;Brown, Birtwistle, Roe, & Thompson, 1999, Brown, Goetz, Van Sciver, Sullivan, & Hamera, 2006Dubbert et al, 2006;Ellingrod et al, 2011;Elmslie, Mann, Silverstone, Williams, & Romans, 2001;Faulkner et al, 2006;Lassenigus, kerlind, Wiklund-Gustin, Arman, & Söderlund, 2013;Lindamer et al, 2008;McLeod, Jaques, & Deane, 2009;Osborn, Nazareth, & King, 2007;Ratliff et al, 2012;Ussher, 2003;Ussher, Doshi, Sampuran, & West, 2011;Van Citters et al, 2010;Vancampfort, Probst, Knapen, Carraro, & De Hert, 2012. Excluded studies (with reason) 55 did not use an outcome measure that provided an assessment of the three fundamental domains of physical activity Acil, Dogan, & Dogan, 2008;Adams, 1995;Aquila, 2000;Archie, Wilson, Osborne, Hobbs, & McNiven, 2003;Ball, Coons, & Buchanan, 2001;Barton, Griffin, & Pretty, 2012;Beebe et al, 2005;Bobes et al, 2010a,b, Bobes, Arango, Garcia-Garcia, & Rejas, 2010bBrill et al, 2007;Brunero & Lamont, 2010;Buhagiar, Parsonage, & Osborn, 2011;Centorrino et al, 2006;Charmove, 1986;Chuang, Mansell, & Pattern, 2008;Crone et al, 2004;Daumit et al, 2005;Davidson et al, 1999Davidson et al, , 2001…”
Section: The Identification Of the Different Outcome Measures Usedmentioning
confidence: 99%
“…One major problem of studies measuring physical activity is the failure of researchers to consider or justify why they have chosen a particular OBM or SRQ. For example past research studies (Archie et al, 2007;Brill et al, 2007;Buhagiar et al, 2011;Chuang et al, 2008;Crone et al, 2004;Daumit et al, 2005;Davidson et al, 1999;Davidson et al, 2001;Ellingrod et al, 2011;Elmslie et al, 2001;Farnam et al, 1999;Lassenigus et al, 2013;McCreadie, 2003;Osborn et al, 2007;Ratliff et al, 2012;Samele et al, 2007;SØrensen, 2006;Van Citters et al, 2010;Vancampfort et al, 2011a,b,c;Vancampfort et al (2011d) have utilised a specific SRQ and justified its choice solely on the original study which validated the SRQ. This is often problematic if the tool has been validated in a certain population or if the original study was not validated correctly.…”
Section: The Problems Regarding the Justification Of Outcome Measure mentioning
confidence: 99%